Myoglobin and Hemoglobin: Discoloration, Lipid Oxidation, and Solvent Access to the Heme Pocket - J Leon Shohet; James G Whalin; Mark Richards; Surendranath P. Suman; Yifei Wang; Yuting Wu (Meat and Muscle Biology, 2023)
Conversion of the heme iron in myoglobin (Mb) and hemoglobin (Hb) from Fe2+ to Fe3+ is a critical step that causes quality deterioration—such as discoloration and generation of oxidative species, including dissociated heme, that oxidize lipids and proteins—in muscle foods. Increased solvent access to the heme pocket has been proposed to cause oxidation of the heme iron and decrease heme affinity for the globin, although empirical results are lacking. This review introduces plasma-induced modification of biomolecules (PLIMB) as an approach to modify amino acids of Mb and Hb and thereby assess solvent access to the heme pocket. After PLIMB, liquid chromatography tandem mass spectrometry peptide analysis and a user-friendly, software platform are used to quantify modified amino acid side chains of the heme proteins. Our findings indicate that PLIMB➔liquid chromatography-tandem mass spectrometry provides a platform to measure solvent access to portions of the heme pocket environment. Evaluation of PLIMB under additional conditions(e.g., different pH values) can differentiate the role of solvent access to the heme pocket relative to the“outer-sphere”mechanism of heme protein oxidation and the ability of hydrogen bonding to stabilize heme within metHb. Some aspects of heme protein-mediated lipid oxidation that occur at low O2partial pressures are discussed in relationship to solvent access to the heme pocket. Other approaches to study mechanisms of discoloration and lipid oxidation related to Mb/Hb oxidation and heme loss from metHb are also discussed.